Introduction to Environmentally Friendly Educational Tourism at Universitas Negeri Semarang for Elementary School - Karsinah; Rahayuningsih, Margareta; Wibawanto, Wandah; Wicaksono, Dimas (Universitas Negeri Semarang, 2024)
Educational tourism or edutourism is a tourism activity that aims to provide learning experiences and skills development. Universitas Negeri Semarang (UNNES) has developed edutourism activities with various themes, but this edutourism is still less well-known to the public. Therefore, the environmentally friendly concept is applied as a characteristic of UNNES edutourism. This activity aimed to increase knowledge, understanding, and skills in developing environmentally friendly edutourism for students. This environmentally friendly edutourism service activity was carried out through three stages, 1) introducing environmentally friendly edutourism, 2) introducing environmentally friendly energy, and 3) activity evaluation. The series of edutourims activities carried out on Wednesday, June 19, 2024, involved elementary school students (SD) who particpated in various activities, including colouring gypsum animal characters to increase creativity and introducing environmeltal conservation, as well as a tour of the Innovation House to understand environmentally friendly energy products. In addition, participants also toured the campus using electric cars that introduced renewable energy applications. The activity results showed that all participants were enthusiastic, understood the environmentally friendly concept, and were interested in participating in similar activities in the future.